2017
DOI: 10.6001/actamedica.v24i2.3489
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macular thickness after trabeculectomy with or without adjunctive 5-fluorouracil

Abstract: Conflict of interest.None of the authors have any conflict of interest to declare, financial or otherwise. No financial or other support was received for the study.Background.The aim of the study was to assess changes in macular thickness after trabeculectomy in respect to the use of 5-fluorouracil (5-FU) as well as to analyse possible associations between the postoperative changes in macular thickness and intraocular pressure (IOP).Materials and methods.The prospective observational study included 106 eyes (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition, changes in the relationship between capillary pressure and interstitial fluid pressure may occur after IOP change. 18,22 In this study, we did not observe any significant change in the mean and sectorial RNFL thickness measured by SS-OCT with surgical IOP reduction. This is in agreement with the findings of previous reports that used scanning laser polarimetry, TD-OCT and SD-OCT. 13,14,23,24 With SD-OCT, Gietzelt et al 13 did not observe significant changes in mean and sectorial RNFL thicknesses between baseline and follow up at 3, 6 and 12 months after trabeculectomy.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…In addition, changes in the relationship between capillary pressure and interstitial fluid pressure may occur after IOP change. 18,22 In this study, we did not observe any significant change in the mean and sectorial RNFL thickness measured by SS-OCT with surgical IOP reduction. This is in agreement with the findings of previous reports that used scanning laser polarimetry, TD-OCT and SD-OCT. 13,14,23,24 With SD-OCT, Gietzelt et al 13 did not observe significant changes in mean and sectorial RNFL thicknesses between baseline and follow up at 3, 6 and 12 months after trabeculectomy.…”
Section: Discussionmentioning
confidence: 48%
“…Kadziauskienė et al also observed a significant increase in mean macular thickness and nine subfields defined by the Early Treatment Diabetic Retinopathy Study (ETDRS) in 106 eyes after 1 week of trabeculectomy. 18 After six months, macula remained thicker only at the central and inner nasal subfields. In our study, the analysis conducted using the SS-OCT commercial software suggests that parameters of the inner macular layers relevant to glaucoma such as total GCL+ and total GCL++, may increase after surgery.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Central macular thickness changes following intraocular surgeries have been shown to impair visual outcomes even in uncomplicated cases. 1 2 3 4 5 Acute reduction of intraocular pressure (IOP) after glaucoma filtering surgery could result in reversible central macular thickening and retinal changes. 5 6 7 8 9 Such macular thickening after glaucoma filtering surgery could be a physiological reaction to the stress of the retina after a sudden reduction of IOP.…”
Section: Introductionmentioning
confidence: 99%